2021
DOI: 10.3389/fneur.2021.722217
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic Sac Drainage Surgery and Plasma Stress Hormone Vasopressin Levels in Meniere's Disease

Abstract: Meniere's disease is a common inner ear disorder accompanied by vertigo attacks and fluctuating hearing loss that some believe is due to a stressful lifestyle. To elucidate the scientific relationship in neuro-endocrinology between Meniere's disease and stress, we examined the surgical results of endolymphatic sac drainage surgery and changes in stress-induced plasma arginine-vasopressin levels. We enrolled 100 intractable Meniere's patients and examined surgical results and plasma vasopressin levels. Fifty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Indeed, the plasma level of vasopressin was increased in patients with MD [ 10 ]. In addition, in patients with intractable MD, plasma vasopressin levels were decreased following endolymphatic sac drainage surgery, which was correlated with recovery from symptoms of MD [ 26 ]. In summary, alcohol consumption could be associated with MD via suppression of diuresis and relief of endolymphatic hydrops.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the plasma level of vasopressin was increased in patients with MD [ 10 ]. In addition, in patients with intractable MD, plasma vasopressin levels were decreased following endolymphatic sac drainage surgery, which was correlated with recovery from symptoms of MD [ 26 ]. In summary, alcohol consumption could be associated with MD via suppression of diuresis and relief of endolymphatic hydrops.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in plasma vasopressin levels after endolymphatic sac drainage in patients with MD suggests that vasopressin may have an effect on patients with MD. [ 24 ] When alcohol is consumed, the dose of vasopressin decreases, [ 25 ] and vasopressin can induce disturbances in patients with endolymphatic hydrops. [ 26 ] Disorder of the endolymphatic fluid is considered the signature feature of MD.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior patterns of patients with MD showed strong tendencies toward engrossment, self-inhibition, feeling pressed for time, and aggressiveness compared to those of controls that engender day-to-day stress and frustration ( 52 ). A recent study on the surgical results of endolymphatic sac drainage surgery and changes in stress-induced plasma arginine-vasopressin levels showed that a gradual plasma vasopressin level elevation in recurrent MD after surgery suggested a link between symptom attacks and internal stress ( 53 ). Although endolymphatic sac drainage surgery was reported to be non-specific for MD and the outcome of the surgery might be linked to other biological effects such as shear stress induced by drilling the mastoid ( 54 , 55 ), the results demonstrating patients without any symptom attacks having significantly low levels of plasma arginine-vasopressin compared to those with symptoms suggest a strong link between symptom attacks and stress ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the surgical results of endolymphatic sac drainage surgery and changes in stress-induced plasma arginine-vasopressin levels showed that a gradual plasma vasopressin level elevation in recurrent MD after surgery suggested a link between symptom attacks and internal stress ( 53 ). Although endolymphatic sac drainage surgery was reported to be non-specific for MD and the outcome of the surgery might be linked to other biological effects such as shear stress induced by drilling the mastoid ( 54 , 55 ), the results demonstrating patients without any symptom attacks having significantly low levels of plasma arginine-vasopressin compared to those with symptoms suggest a strong link between symptom attacks and stress ( 53 ). It was also reported that acute stress affects endocrine, immune, and metabolic functions in humans, and mood plays a causal role in the modulation of responses to acute stress ( 56 ).…”
Section: Discussionmentioning
confidence: 99%